Optimasi Lebar Celah Udara Generator Axial Magnet Permanen Putaran Rendah 1 Fase - Hari Prasetijo; Sugeng Waluyo (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
This study designs a 1-phase permanent magnet generator with double-sided axial coreless 10 stator poles to get optimum output voltage and power. Permanent magnet generator is chosen because it does not require a DC excitation current and the maintenance is relatively easy, so it has potential to be applied on a low head pico hydro power plant. The design uses NdFeb (Neodymium-Iron-Boron) type permanent magnet. The study was conducted by simulation to get the flux density in the stator coil using FEMM 4.2 applications. Simulation is done with the air gap width varies from 2 mm, 3 mm, 4 mm, and 5 mm. The depth of the magnet in the yoke varies from 0%, 5%, 10%, and 50% of the magnet thickness. Then, the flux density is used to estimate the output voltage and power of the generator. The results show that minimum output of 52.85 V and 195,56 VA is obtained at air gap distance of 5 mm and the depth of the magnet in yoke is 50%. Maximum output of 87,25 V and 322.84 VA is obtained at air gap distance of 2 mm and the depth of the magnet in yoke is 0% of the magnet thickness.